"Minorities: The Mirror of Society" - California Council for the Social Studies Annual Conference, 1969 - Galarza, Ernesto:::creator::::::::::::
Speech given by Dr. Ernesto Galarza at the annual California Council for the Social Studies, held in 1969. In this speech, Dr. Galarza examines the concept of minorities, particularly Mexican-Americans, and their societal roles and challenges. He criticizes the classification of minorities based on numbers, arguing that the social realities and significance of these groups extend beyond statistics. Galarza discusses the complexities within the Mexican-American community, noting various subgroups, and explains that these internal differences challenge the notion of a homogeneous minority.